Histopathology of fallopian tubes: a study in the age group of 35 – 50 years in a metropolis of Eastern India - Mondal, Hironmoy; Kumar Khanra, Santanu; Meyur, Rudradev; Sadhu, Anirban; De, Alpana; Das, Rupkamal (International Journal of Medical Research and Review, 2016)
Introduction: Diseases of fallopian tubes are not very commonly described in world literature. However they very commonly form surgical specimen in various treatment modalities of females. Hence it appears prudent enough to shed some light on diseases of fallopian tubes through histological study. The aim and objectives of this study therefore was to identify the various types of diseases of fallopian tubes based on histology. Materials and methods: 106 cases with 204 fallopian tubes from females in the age group of 35 – 50 years were selected for the study and examined under the light microscope after staining with H & E. The findings were then documented for analysis and discussion. The study was conducted in a medical college of Kolkata. Results: The majority of cases presented with menorrhagia. TAH with BSO was the most common operative procedure performed to collect specimen. Histology revealed normal tubes in most of the cases. The findings were displayed in tabular form and relevant discussion was included. Conclusion(s): The findings of the present study are similar to those of other authors. Differences can be attributed to smaller sample size and population characteristics.